Efficacy and Safety of Ciprofol for Anesthesia in Painless Colonoscopy with Varying Body Mass Indices Patients: A Prospective, Single-Center, Observational Study - Li Y; Yuan M; Zhang P; Zhou T; Zhang M; Xu J (Drug Design, Development and Therapy)
Yaqi Li, Mailong Yuan, Ping Zhang, Tao Zhou, Mingsheng Zhang, Jinhui Xu Department of Anesthesiology, Jiangxi Provincial People’s Hospital, The First Affiliated Hospital of Nanchang Medical College, Nanchang, Jiangxi, 330006, People’s Republic of ChinaCorrespondence: Jinhui Xu, Department of Anesthesiology, Jiangxi Provincial People’s Hospital, The First Affiliated Hospital of Nanchang Medical College, Nanchang, 330006, People’s Republic of China, Email mzkxjh@163.comBackground: Ciprofol, a novel intravenous anesthetic derived from propofol, exhibits high lipophilicity. Its pharmacokinetics and pharmacodynamics may vary across different body mass indices (BMI) categories, but data on its optimal dosing as well as its safety and efficacy during colonoscopy anesthesia in varying BMI groups are lacking.Objective: To evaluate the efficacy and safety of ciprofol during anesthesia for painless colonoscopy in patients with varying BMI, and to explore the correlation between BMI and induction dose.Methods: The BMI classification standard used in this study followed the criteria used in China. This prospective, single-center, observational study enrolled two hundred patients and they were divided into three groups with BMI: Group A (18.5– 23.9 kg/m²), Group B (24– 27.9 kg/m²), and Group C (28– 39.9 kg/m²). Ciprofol was administered slowly (3 seconds per milliliter) until MOAA/S ≤ 1. Induction dose, additional ciprofol use, procedure duration, recovery time, vital signs, and adverse events were recorded.Results: The total induction dose was higher in Groups B and C than in Group A, with Group C receiving the highest dose (P< 0.001). Dose per kilogram of TBW was lower in Groups B and C (P< 0.001), while corrected body weight (CBW)-based dosing showed no significant difference between groups (P=0.287). There were no significant differences in procedure duration, recovery time, or adverse events among groups.Conclusion: Ciprofol is safe and effective for colonoscopy anesthesia across BMI groups, offering stable hemodynamics without prolonging recovery or increasing adverse events. CBW is a reliable dosing metric for overweight and obese patients.Keywords: ciprofol, body mass index, colonoscopy, anesthesia